Zα domain proteins mediate the immune response - Zhong, Yuhan; Zhong, Xiao; Qiao, Liangjun; Wu, Hong; Liu, Chang; Zhang, Ting (Frontiers in Immunology, 2023)
The Zα domain has a compact α/β architecture containing a three-helix bundle flanked on one side by a twisted antiparallel β sheet. This domain displays a specific affinity for double-stranded nucleic acids that adopt a left-handed helical conformation. Currently, only three Zα-domain proteins have been identified in eukaryotes, specifically ADAR1, ZBP1, and PKZ. ADAR1 is a double-stranded RNA (dsRNA) binding protein that catalyzes the conversion of adenosine residues to inosine, resulting in changes in RNA structure, function, and expression. In addition to its editing function, ADAR1 has been shown to play a role in antiviral defense, gene regulation, and cellular differentiation. Dysregulation of ADAR1 expression and activity has been associated with various disease states, including cancer, autoimmune disorders, and neurological disorders. As a sensing molecule, ZBP1 exhibits the ability to recognize nucleic acids with a left-handed conformation. ZBP1 harbors a RIP homotypic interaction motif (RHIM), composed of a highly charged surface region and a leucine-rich hydrophobic core, enabling the formation of homotypic interactions between proteins with similar structure. Upon activation, ZBP1 initiates a downstream signaling cascade leading to programmed cell death, a process mediated by RIPK3 via the RHIM motif. PKZ was identified in fish, and contains two Zα domains at the N-terminus. PKZ is essential for normal growth and development and may contribute to the regulation of immune system function in fish. Interestingly, some pathogenic microorganisms also encode Zα domain proteins, such as, Vaccinia virus and Cyprinid Herpesvirus. Zα domain proteins derived from pathogenic microorganisms have been demonstrated to be pivotal contributors in impeding the host immune response and promoting virus replication and spread. This review focuses on the mammalian Zα domain proteins: ADAR1 and ZBP1, and thoroughly elucidates their functions in the immune response.